The influence of the therapist's activities on clients' subject positioning in relation to gender in narrative couples therapy - Friis, Kirsten Leigh (Rhodes University, Faculty of Humanities, Department of Psychology, 2014)
Narrative Therapy draws on an understanding of how discourse acts to construct, reproduce and deconstruct power relationships. Therapy is focussed on collaborating with clients in a process of re-authoring their self-stories by critically evaluating the positions made available to them in relation to dominant discourses. Whilst there is a large body of theoretical knowledge on post-structuralism and psychotherapy, very few discourse analyses of psychotherapy sessions have been published. Thus, though post-structuralist therapeutic approaches are theoretically well supported, there is an identified gap in the literature on the therapeutic processes that occur within practice. This research aims to further explore these therapeutic processes, focussing specifically on subject positioning with relation to gender in Narrative Couple Therapy, and the influence of the therapist thereupon. It is based on the analysis of a video of a Michael White Narrative Couple Therapy session, "The Best of Friends." Using discourse analysis as a methodological approach, the analysis seeks first to identify talk that signifies discourses of gender difference, and then to explore how the subjects (therapist and clients) are positioned in relation to these discourses. The analysis focuses on the therapist's activities to investigate the influence of his interactions with the partners on how they are positioned or position themselves within stories of gender difference. The analysis shows that, by working reflexively, transparently and collaboratively with the partners, the therapist assists to render power, restrictive discourses, and alternate positions visible to the clients. The therapist resists being drawn into dominant therapy discourses of expert and patient, and instead continuously recognises the knowledges and expertise that the clients bring to the therapy context. He then works closely with the clients to thicken alternative representations of self.
Keywords: Narrative therapy; Couples therapy; Therapist and patient; Control (Psychology); Critical discourse analysis; Psychotherapy -- Methods